Gerabah Dan Kajian Kawasan: Studi Kasus Kompleks Kebudayaan Buni Jawa Barat - Sumijati Atmosudiro (Berkala Arkeologi, 1995)
In line with the development of Indonesian archaeological research, the direction of research that was initially focused only on site studies, needs to be expanded towards regional or regional-scale studies. Area-scale studies in addition to being able to reconstruct past lives, can also reveal cultural changes. Thus the results of area-scale research can reveal two archaeological paradigms.